From Literacy to Inclusion: The Role of Financial Consultants in Improving Financial Accessibility and Well-being - Romi Kurniadi; Dwi Rayana Siregar; Sri Wahyuni; Sudawan Supriadi; Fadilla Ulfah; Destri Yaldi (Yayasan Keluarga Guru Mandiri, 2025)
Financial literacy is critical to enhancing the financial well-being of individuals and families, yet a strong understanding alone does not guarantee effective financial decision-making. Financial consultants are key in bridging the gap between knowledge and action. This study analyzes recent trends in financial consultant services and financial literacy using a PRISMA-based systematic review method. Data were gathered from multiple scholarly databases and analyzed through bibliometric techniques to identify publication patterns and keyword relationships. Results reveal that individuals with high financial literacy are more likely to seek professional advice, while those with low literacy levels remain hesitant. Financial technologies such as robo-advisors have emerged as complementary tools but have not replaced human advisors. The study concludes that strengthening regulations, expanding access to financial consulting for lower-middle-income groups, and integrating technology are essential strategies. This research contributes to the scientific field by highlighting the interplay between financial literacy, advisory services, and technology, offering a pathway to more inclusive financial well-being.